Genus bacillus, promising probiotics in aquaculture: Aquatic animal origin, bio-active components, bioremediation and efficacy in fish and shellfish - Soltani, Mehdi; Ghosh, Koushik; Hoseinifar, Seyed Hossein; Kumar, Vikash; Lymbery, Alan J.; Roy, Suvra; Ringø, Einar (Reviews in Fisheries Science & Aquaculture, 2019)
Species of Bacillus are spore-forming bacteria that are resistant to aggressive physical and chemical conditions, with various species showing unusual physiological features enabling them to survive in various environmental conditions including fresh waters, marine sediments, desert sands, hot springs, Arctic soils, and the gastrointestinal tract of finfish and shellfish. They are able to rapidly replicate and tolerate a multitude of environmental conditions, giving a wide range of beneficial effects in the aquaculture sector. Application of Bacillus spp. as probiotics in feed or for bioremediation of aquaculture rearing water has great potential for sustainable aquaculture. Species of Bacillus may play a desirable role in removing waste products from aquaculture environments, maintaining optimum water quality, and reducing stress, which can lead to an improved immuno-physiological balance, better growth and enhanced survival in target aquatic animals. Application of probiotic Bacillus spp. can enhance growth and immune function of aquatic organisms. Probiotic Bacillus can also assist in maintaining a higher density of beneficial bacteria and a lower load of pathogenic agents in aquaculture ponds. Much is still unknown, however, about how the probiotic efficacy of specific Bacillus species is affected by different aquatic animal species, age and growth condition, water quality, and diet. Also, the details of mode of actions of Bacillus spp. on the immune-physiological functions of aquatic organisms as well as their functions as bioremediators of water quality need further studies. This review addresses the presence of Bacillus spp. in the gastrointestinal tract of finfish and shellfish, their ability to produce enzymes and antibacterial compounds, and their efficacy and potency as probiotics in aquaculture.